2014
DOI: 10.4103/1305-7456.143614
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of cementum-extended composite fillings in severely damaged deciduous incisors: An in vitro study

Abstract: Objective:The aim of this study was to comparatively assess the fracture resistance of the cementum-extended and conventional composite fillings with or without intracanal composite posts in severely damaged deciduous incisors.Materials and Methods:This in vitro study was performed on 60 extracted deciduous maxillary incisors that were randomly divided into four groups: Group 1: Composite filling (CF); Group 2: Composite filling with composite posts (CF + CP); Group 3: Composite filling extended 0.5 mm to ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…The statistical tests found no significant difference in fracture strength of RMGIC and composite resin groups. In our study, fracture strength in composite resin group was lower than that in the study by Seraj et al [20,23] and higher than that in the study by Island and White [21]. Difference in fracture strength in different studies may be due to the variability in size of teeth, direction of applied load and type of restorative material used for reconstruction of crown and fabrication of intracanal post.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The statistical tests found no significant difference in fracture strength of RMGIC and composite resin groups. In our study, fracture strength in composite resin group was lower than that in the study by Seraj et al [20,23] and higher than that in the study by Island and White [21]. Difference in fracture strength in different studies may be due to the variability in size of teeth, direction of applied load and type of restorative material used for reconstruction of crown and fabrication of intracanal post.…”
Section: Discussioncontrasting
confidence: 68%
“…Several methods with similar efficacy have been introduced to obtain retention from the canal [9][10][11][12][13][14][15][16][17][18][19]. Evidence shows that intracanal extension of composite material can significantly increase the retention compared to extension of restoration to the cementum [20]. Aside from providing adequate retention for coronal restoration, adequate fracture strength is another important criterion for success of restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] In primary teeth, it should not interfere with root resorption and the physiological eruption of permanent teeth. [13] Hence, the length of the post was restricted to 3 mm. The present in vitro study has yielded the fracture resistance values between 28 N and 275 N. In contrast, permanent teeth studies have shown higher fracture resistance ranging from 400 N to 935 N. The high value was due to larger diameter of the permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…in 2010, the levels of bite force in primary anterior teeth ranged between 6.87 N to 140.09 N.[16] This range is similar to our compressive strength values which ranged between 28 N to 275 N. In contrast, Seraj et al . [13] have quoted higher values in cementum-extended composite post system which was 601 N. The authors explained that the higher value was due to ferrule effect. The wide range in fracture resistance values in our study was due to variation in sample sizes (incisors and canines were of different length and diameter).…”
Section: Discussionmentioning
confidence: 99%